The effect of the blood glucose concentration on night work nurses’ attention . - Shokrollahi, Fereydoon; Mahmoudi, Hossein; Ebadi, Abas; Najafi mehri, Soheil; Jafari, Mahvash (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim: The repairing effect of glucose on brain cognition functioning, especially attention has been studied widely.Cognitive performance and attention is a vital aspect in nursing practice. Decreased attention and nursing errors may result in substantial mortality, morbidity, and additional health care costs. The aim of this study was to determine the effect of the blood glucose concentration on night work nurses’ attention accuracy in military hospitals in Tehran ,Iran. Materials and Methods: A quasi-experimental study was carried out. A convenience sample of 60 nurses working in, two military hospitals in Tehran participated in the study. These nurses were randomly allocated in intervention and control groups. The study was carried out from Sep2009 to April 2010. Data were collected using a demographic data form and attention accuracy was evaluated by Toulouse- Pieron and Bonnardel test. Data collection and intervention was carried out during 4 to 5 am. The blood glucose concentration was measured before intervention, then nurses in intervention group received PQ gr glucose solution, and nurses in control group drank water. One hour after intervention attention accuracy and blood glucose reevaluated in both groups. Data were analyzed by SPSS V.15 software. Findings: The results indicated that glucose consumption improved the attention accuracy of nurses (P<0.001). Conclusion : Based on the results, glucose consumption or carbohydrate diet in night work nursing effects on brain cognition performance especially accuracy. Keywords: Glucose, accuracy, nurse, night work shift REFERENCES -Atkinson R L et al (2009). [Hilgards introduction to psychology] Translated by Baraheni et al, Tehran, Roshd publisher (Persian). -Abedi M (2008). [Laboratory Methods & Diagnosis] 6 th edition, Tehran, Noordanesh Publisher (Persian). -Benton D Parker PY (1998). Breakfast, blood glucose, and cognition. American Journal of Clinical Nutrition. 67 (4) 772S. -Benton D Owens DS Parker PY (1994). Blood glucose influences memory and attention in young adults. Neuropsychology. 32 (5) 595-608. -Benton D Parker P Donohoe R. (2008). The supply of glucose to the brain and cognitive functioning. Journal of Biosocial Science. 28 (04) 463-79. -Benton D Owens DS Parker PY (1994). Blood glucose influences memory and attention in young adults. Neuropsychology. 32 (5) 595-608. -Balas MC Scott LD Rogers AE (2004). The prevalence and nature of errors and near errors reported by hospital staff nurses. Applied Nursing Research. 17 (4) 224-30. -Benner P Sheets V Uris P Malloch K Schwed K Jamison D Individual, practice, and system causes of errors in nursing: taxonomy. Journal of Nursing Administration. 2002. 32 (10) 509. -Cromer B et al (1990). The school breakfast program and cognition in adolescents. Journal of Developmental & Behavioral Pediatrics. 11(6) 295. -Devlin T M. (2006). Textbook of Biochemistry with Clinical Correlations 6th ed, USA, Wiley-Liss, AJOHN WILEY & SONS Publisher. -Di Bonito P et al (2007). Impact of impaired fasting glucose and other metabolic factors on cognitive function in elderly people. Nutrition, Metabolism and Cardiovascular Diseases. 17 (3) 203-8. -Dawson B & Trapp R (1997). [Basic and clinical biostatistics ] 4th edition translated by sarafraz et al, Mashhad, Mashhad University of Medical Sciences and Health services Publisher (Persian). -Daly LE Bourke GJ Mcgilvray J (1997). [Interpretation and uses of medical statistics] 4th edition, translated by faghihzadeh Tehran, Shahed University Publisher (Persian). -Ebrahimian A (2006). [Night work Nursing: The level of attention]. Payesh. 5 (2) 123-130 (Persian). -Fischer K et al (2002). Carbohydrate to protein ratio in food and cognitive performance in the morning. Physiology and Behavior. 75 (3) 411-24. -Guyton AC Hall JE (2008). Text book of Medical Physiology 11th ed, Philadelphia, Pennsylvania, Elsevier-Saunders Publisher. -Gold P (2005). Glucose and age-related changes in memory. Neurobiology of aging. 26 (1) 60-4. -Gold P (2004). Coordination of multiple memory systems. Neurobiology of learning and memory. 82 (3) 230-42. -Ganji H (2009). [Work Psychology] 11th ed, Tehran, Nashr-Savalan Publisher (Persian). -Ganji H (2007). [Psychology of Individual Differences] 12th ed, Tehran, Besat Publisher (Persian). -Gulpinar M Yegen B (2004). The physiology of learning and memory: role of peptides and stress. Current Protein and Peptide Science. 5 (6) 457-73. -Holt S (1999). The effects of high-carbohydrate vs. high-fat breakfasts on feelings of fullness and alertness, and subsequent food intake. International Journal of Food Sciences and Nutrition. 50 (1) 13-28. -Hoyland A Lawton C Dye L (2008). Acute effects of macronutrient manipulations on cognitive test performance in healthy young adults: A systematic research review. Neuroscience & Biobehavioral Reviews. 32 (1) 72-85. -Hashemi F (2008). [Ethical response to nursing error]. Journal of Medical Ethics and History of Medicine. 1 (4) 32- 42(Persian). -Keyhani M Shariatpanahi M (2008). [Assessment of music effect on concentration and attention among students of Azad] University of Medical Sciences]. Tehran unit. 18 (2) 101-106. (Persian). -Kaplan RJ et al (2001). Dietary protein, carbohydrate, and fat enhance memory performance in the healthy elderly. American Journal of Clinical Nutrition. 74 (5) 687. -Khodarahmi R Bahrami N (2003). [Metabolism] 1 st edition, Tehran, Noor-e-Danesh Publisher (Persian). -Luriia, A. (1989). [The working brain] 1 st edition Translated by Monajem, Tehran, Bonyad Publisher (Persian). -Lloyd H et al (1996). Acute effects on mood and cognitive performance of breakfasts differing in fat and carbohydrate content. Appetite. 27 (2) 151-64. -McAulay V et al (2001). Acute hypoglycemia in humans causes attention dysfunction while nonverbal intelligence is preserved. Diabetes Care. 24 (10) 1745. -Messier C (2004). Glucose improvement of memory: a review. European journal of pharmacology. 490 (1-3):33-57. -McNay E Gold P (2002). Food for thought: fluctuations in brain extracellular glucose provide insight into the mechanisms of memory modulation. Behavioral and Cognitive Neuroscience Reviews. 1(4) 264. -Men D McCarty R Gold P (1999). Enhanced release of nor epinephrine in rat hippocampus during spontaneous alternation tests. Neurobiology of learning and memory. 71(3) 289-300. -Owens DS Benton D (1994). The impact of raising blood glucose on reaction times. Neuropsychobiology. 30 (2) 106- 13. -Richards M (1972). Studies on breakfast and mental performance. International Journal of Food Sciences and Nutrition. 26 (4) 219-23. -Rolandsson O et al. (2008). Increased glucose levels are associated with episodic memory in no diabetic women. Diabetes. 57 (2) 440. -Scholey AB et al. (2009). Glucose administration prior to a divided attention task improves tracking performance but not word recognition: evidence against differential memory enhancement? Psychopharmacology. 202 (1) 549-58. -Smith A et al (1994). Effects of breakfast and caffeine on cognitive performance, mood and cardiovascular functioning. Appetite. 22 (1) 39-56. -Stefani M Nicholson G Gold P (1999). ATP-sensitive potassium channel blockade enhances spontaneous alternation performance in the rat: a potential mechanism for glucose-mediated memory enhancement. Neuroscience. 93 (2) 557- 63. -Smith M Foster J (2008). Glucoregulatory and order effects on verbal episodic memory in healthy adolescents after oral glucose administration. Biological Psychology. 79 (2) 209-15. -Sagoe-Moses C et al (2001). Risks to health care workers in developing countries. New England Journal of Medicine. 345 (7)538. -Sünram-Lea S Dewhurst S Foster J (2008). The effect of glucose administration on the recollection and familiarity components of recognition memory. Biological Psychology. 77 (1) 69-75. -Vanhanen M et al (1998). Cognitive function in an elderly population with persistent impaired glucose tolerance. Diabetes Care. 21(3) 399. -Vaisman N et al (1996). Effect of breakfast timing on the cognitive functions of elementary school students. Archives of pediatrics & adolescent medicine. 150 (10) 1089.